Photocatalysts, methods of making the same, methods and systems for testing photocatalytic carbon dioxide reduction yield

CN120714704BActive Publication Date: 2026-10-27TSINGHUA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510851856.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2026-10-27
Estimated Expiration
2045-06-24

AI Technical Summary

Technical Problem

然而,该技术在实际应用中仍面临诸多挑战:首先是光催化材料性能不足

Benefits of technology

[0013]本申请通过上述方法将双铜配合物组装到石墨相氮化碳载体上,获得了兼具高效光生电荷分离能力、高产物选择性及良好稳定性的光催化剂,且原料价廉、工艺简单,有效降低了产品成本,适合于工业化大批量生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120714704B_ABST
    Figure CN120714704B_ABST
Patent Text Reader

Abstract

The application discloses a photocatalyst, a preparation method thereof, a method and a system for testing a carbon dioxide reduction yield of the photocatalyst, and the photocatalyst comprises a graphite phase carbon nitride carrier and a double copper complex, and the double copper complex is at least partially loaded on the surface of the graphite phase carbon nitride carrier. Therefore, the photocatalyst has the advantages of wide spectrum response, high efficient photo-induced charge separation capacity, high product selectivity and good stability, and simple and low-cost preparation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of photocatalytic materials technology, specifically to photocatalysts and their preparation methods, as well as methods and systems for testing the photocatalytic carbon dioxide reduction yield. Background Technology

[0002] Photocatalytic CO2 reduction technology can directly utilize solar energy to drive the reaction, converting CO2 into high-value-added chemicals (such as methane and ethylene). Its green and sustainable characteristics have attracted considerable attention. However, this technology still faces many challenges in practical applications: First, the performance of photocatalytic materials is insufficient. Traditional semiconductor photocatalysts (such as TiO2 and ZnO) have a narrow light response range, mainly limited to the ultraviolet region, and their high electron-hole recombination rate leads to low quantum efficiency. Second, product selectivity is poor. Most catalysts have limited ability to selectively regulate CO2 reduction products, making it difficult to efficiently generate high-value-added C2 products (such as ethylene), and resulting in numerous byproducts (such as CO and H2). Finally, there are issues of catalyst stability and cost. Some catalysts (such as noble metal-based materials) have high activity but are expensive; while some non-noble metal catalysts (such as graphene-phase carbon nitride (g-C3N4)) have good chemical stability, but their small specific surface area and low carrier separation efficiency make them difficult to meet the needs of industrial applications. Therefore, developing a CO2 photoreduction catalyst that combines high efficiency in photogenerated charge separation, high product selectivity, and good stability, and achieving its simple and low-cost preparation, remains a technical challenge that urgently needs to be solved in this field.

[0003] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention

[0004] In a first aspect, this application proposes a photocatalyst comprising: a graphitic carbon nitride support and a copper complex, wherein the copper complex is at least partially loaded on the surface of the graphitic carbon nitride support. Thus, this photocatalyst exhibits a broad spectral response, efficient photogenerated charge separation capability, high product selectivity, and good stability.

[0005] In addition, the photocatalyst according to the above embodiments of this application may also have the following additional technical features:

[0006] In some embodiments of this application, the mass ratio of the graphite-phase carbon nitride support to the copper bis-copper complex is 1:(0.1–0.4). This allows for a more complete reaction and reduces raw material waste.

[0007] In some embodiments of this application, the ligand of the bis-copper complex includes 2,2'-bipyridine-4,4'-diphosphonic acid. This is beneficial for improving the catalytic activity of the bis-copper complex.

[0008] In some embodiments of this application, in the conjugated framework of the graphitic carbon nitride support, cyano groups are bonded to the carbon atom sites of the triazine ring in a terminal modification manner. This is beneficial for improving the absorption of visible light and the ion separation efficiency of the graphitic carbon nitride support.

[0009] In some embodiments of this application, the double copper complex is coupled to the surface of the graphitic carbon nitride support through a combination of hydrogen bonding and π-π stacking. This is beneficial for improving the catalytic activity and product selectivity of the photocatalyst.

[0010] In a second aspect of this application, a method for preparing a photocatalyst is provided, comprising:

[0011] The copper complex and the graphite-phase carbon nitride support were dispersed in methanol and stirred to obtain a precipitate.

[0012] The precipitate was washed and dried sequentially to obtain the photocatalyst.

[0013] This application uses the above method to assemble a double copper complex onto a graphitic carbon nitride support, thereby obtaining a photocatalyst that combines high efficiency in photogenerated charge separation, high product selectivity, and good stability. Moreover, the raw materials are inexpensive and the process is simple, which effectively reduces product costs and makes it suitable for large-scale industrial production.

[0014] In some embodiments of this application, the method for preparing the bis-copper complex includes: mixing a copper-containing compound, 2,2'-bipyridine-4,4'-diphosphonic acid, and oxalate dihydrate in a molar ratio of (1.995-2.005):(1.995-2.005):1 to obtain a mixture; reacting the mixture at 60°C–80°C and pH 3–5 for 3–10 h; and drying to obtain the bis-copper complex. This process can impart phosphate groups to the bis-copper complex, which is beneficial for loading the bis-copper complex onto a graphitic carbon nitride support.

[0015] In some embodiments of this application, the copper-containing compound includes at least one of CuCl2·2H2O, CuSO4·5H2O, and Cu(CH3COO)2·2H2O. Therefore, a wider range of raw materials can be used, and the cost is lower.

[0016] In some embodiments of this application, the method for preparing the graphitic carbon nitride support includes: using an ammonia-containing organic compound as a precursor, obtaining a graphitic carbon nitride matrix through prepolymerization and a first calcination treatment; and mixing the graphitic carbon nitride matrix with a mixed molten salt for a second calcination treatment to obtain the graphitic carbon nitride support. This allows the introduction of cyano groups into the graphitic carbon nitride support, resulting in a wider visible light absorption range.

[0017] In some embodiments of this application, the ammonia-containing organic compound includes at least one selected from urea, melamine, thiourea, dicyandiamide, cyanamide, and cyanuric acid. Therefore, a wide variety of precursors can be used, and the cost is relatively low.

[0018] In some embodiments of this application, the prepolymerization temperature is 200℃~300℃, and the first calcination treatment temperature is 450℃~650℃. Prepolymerization can promote the initial condensation of the precursor, reduce excessively rapid volatilization caused by direct high-temperature calcination, and simultaneously repair structural defects, improve crystallinity, and enhance stability through the first calcination treatment.

[0019] In some embodiments of this application, the temperature of the second calcination treatment is 500°C to 800°C. This is beneficial for improving the crystallinity of the graphitic carbon nitride support.

[0020] In some embodiments of this application, the mass ratio of the graphitic carbon nitride matrix to the mixed molten salt is 1:(2.5-10). This increases the reaction rate and reduces raw material waste.

[0021] In some embodiments of this application, the mixed molten salt includes a mixed molten salt of sodium chloride and lithium chloride, a mixed molten salt of lithium nitrate and potassium nitrate, a mixed molten salt of lithium carbonate and potassium carbonate, or a mixed molten salt of lithium chloride, potassium chloride, and lithium carbonate. Therefore, a wide variety of mixed molten salt systems can be selected, resulting in lower costs.

[0022] In some embodiments of this application, the molar ratio of sodium chloride to lithium chloride in the mixed molten salt of sodium chloride and lithium chloride is 1:(0.5-4). This facilitates completing the reaction at a lower temperature.

[0023] In a third aspect of this application, a method for testing the yield of photocatalytic carbon dioxide reduction is proposed, comprising:

[0024] The photocatalyst described in the first aspect of this application or the photocatalyst prepared by the method described in the second aspect of this application is dispersed in water to form a suspension.

[0025] The suspension is placed in a quartz reactor and carbon dioxide is introduced into the quartz reactor to purge air.

[0026] The suspension was irradiated with a light source to carry out a photocatalytic reaction, and the gaseous products were sampled during the reaction.

[0027] The gaseous products were analyzed using an online gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector.

[0028] This application employs an online gas chromatograph equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD) to simultaneously detect hydrocarbon products (such as CH4 and C2H4) and inorganic products (such as CO and H2), enabling precise quantitative analysis of the products. Standardized test conditions ensure data comparability, and precise temperature and flow control guarantee experimental repeatability.

[0029] In some embodiments of this application, the analytical conditions of the online gas chromatograph include: helium as the carrier gas, a flow rate of 5 mL / min to 30 mL / min; and a column temperature program of 80°C for 5 minutes, followed by an increase to 200°C at a rate of 10°C / min. Precise temperature and flow rate control ensures experimental repeatability.

[0030] In a fourth aspect, this application proposes a system for photocatalytic carbon dioxide reduction, comprising: the photocatalyst described in the first aspect of this application, a quartz reactor, a gas circulation device, and a xenon lamp light source equipped with a 420nm cutoff filter. Thus, this system can achieve efficient and stable photocatalytic carbon dioxide reduction. Attached Figure Description

[0031] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0032] Figure 1 This is a process flow diagram illustrating the preparation of a graphite-phase carbon nitride matrix, a carbon nitride support, a double copper complex, and a Cu2L / mCN photocatalyst according to an embodiment of this application.

[0033] Figure 2 This is a transmission electron microscope image of a graphitic carbon nitride matrix according to an embodiment of this application;

[0034] Figure 3 This is a high-resolution transmission electron microscope image of a carbon nitride support according to an embodiment of this application;

[0035] Figure 4 This is a transmission electron microscope image of a copper-based complex according to an embodiment of this application;

[0036] Figure 5 Here is a Fourier transform infrared spectrum of a copper-based complex and its related precursor according to an embodiment of this application;

[0037] Figure 6 This is a high-angle annular dark-field scanning transmission electron microscope image of a Cu2L / mCN photocatalyst according to an embodiment of this application;

[0038] Figure 7 X-ray diffraction pattern of carbon nitride support, double copper complex, and Cu2L / mCN photocatalyst according to an embodiment of this application;

[0039] Figure 8 Fourier transform infrared spectra of carbon nitride support, double copper complex, and Cu2L / mCN photocatalyst according to an embodiment of this application;

[0040] Figure 9 The UV-Vis diffuse reflectance absorption spectra of a graphitic carbon nitride matrix, a carbon nitride support, and a Cu2L / mCN photocatalyst according to an embodiment of this application are shown.

[0041] Figure 10 This is a comparison diagram of the photocatalytic activity of a Cu2L / mCN photocatalyst according to one embodiment of this application;

[0042] Figure 11 Cyclic stability curves for photocatalytic reduction of CO2 tested from a Cu2L / mCN photocatalyst of one embodiment of this application;

[0043] Figure 12 The image shows the XRD pattern of a recovered sample of Cu2L / mCN photocatalyst from one embodiment of this application after four cycles of photocatalytic reduction of CO2.

[0044] Figure 13 This is a schematic diagram of the structure of a Cu2L / mCN photocatalyst synthesized according to an embodiment of this application. Detailed Implementation

[0045] The embodiments of this application are described in detail below, with examples of these embodiments shown in the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0046] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0047] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.

[0048] In the description of this application, all figures disclosed herein are approximate, whether or not the words "approximately" or "about" are used. Each figure may vary by less than 10% or by a difference that is considered reasonable by a person skilled in the art, such as 1%, 2%, 3%, 4%, or 5%.

[0049] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. "First feature" and "second feature" may include one or more of the indicated feature.

[0051] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.

[0052] In this application, the order in which the steps are written does not imply a strict execution order and does not limit the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application can be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0053] The g-C3N4-based catalysts in related technologies have the following drawbacks:

[0054] (1) Defects in light absorption performance: The visible light absorption range is ≤450nm, resulting in insufficient utilization of sunlight;

[0055] (2) Charge separation defects: Carrier separation efficiency <10%, low photon efficiency;

[0056] (3) Product selectivity defects: The proportion of C1 products in CO2 reduction products is >85%, and the selectivity of C2 products is <15%.

[0057] To address the aforementioned technical deficiencies, this application employs a molten salt method to prepare a short-range ordered graphitic carbon nitride support (mCN), which is then combined with a self-assembled copper complex (Cu2L) through hydrogen bonding and π-π stacking interactions to obtain a Cu2L / mCN photocatalyst. This results in a photocatalyst with broad spectral response, high charge separation efficiency, and excellent C2 product selectivity.

[0058] In a first aspect of this application, a photocatalyst is proposed, comprising: a graphitic carbon nitride support and a copper complex, wherein the copper complex is at least partially supported on the surface of the graphitic carbon nitride support. Thus, this photocatalyst exhibits a broad spectral response, efficient photogenerated charge separation capability, high product selectivity, and good stability.

[0059] In addition, the photocatalyst according to the above embodiments of this application may also have the following additional technical features:

[0060] In some embodiments of this application, the mass ratio of the graphite-phase carbon nitride support to the copper bis-copper complex is 1:(0.1–0.4), for example, 1:0.1, 1:0.2, 1:0.3, or 1:0.4. This allows for a more complete reaction and reduces raw material waste.

[0061] In some embodiments of this application, the ligands of the bis-copper complex include 2,2'-bipyridine-4,4'-diphosphonic acid. This is beneficial for improving the catalytic activity of the bis-copper complex.

[0062] In some embodiments of this application, in the conjugated backbone of the graphitic carbon nitride support, cyano groups are bonded to the carbon atom sites of the triazine ring in a terminal modification manner. This is beneficial for improving the absorption of visible light and the ion separation efficiency of the graphitic carbon nitride support.

[0063] In some embodiments of this application, the double copper complex is coupled to the surface of the graphitic carbon nitride support through a combination of hydrogen bonding and π-π stacking. This is beneficial for improving the catalytic activity and product selectivity of the photocatalyst.

[0064] In a second aspect of this application, a method for preparing a photocatalyst is provided, referring to... Figure 1 and Figure 13 ,include:

[0065] S1: The double copper complex and the graphite-phase carbon nitride support were dispersed in methanol and stirred to obtain a precipitate.

[0066] In some embodiments of this application, the method for preparing the bis-copper complex includes: mixing a copper-containing compound, 2,2'-bipyridine-4,4'-diphosphonic acid, and oxalic acid dihydrate in a molar ratio of (1.995-2.005):(1.995-2.005):1 (e.g., 1.995:1.995:1, 2:2:1, or 2.005:2.005:1, etc.) to obtain a mixture; reacting the mixture at 60°C–80°C (e.g., 60°C, 70°C, or 80°C, etc.) and pH 3–5 for 3–10 h (e.g., 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h, etc.), centrifuging, and then drying (e.g., freeze-drying) to obtain the bis-copper complex. Wherein, 2,2'-bipyridine-4,4'-diphosphonic acid is a chelating ligand, oxalic acid is a bridging agent, and Cu... 2+ In aqueous solution, a [Cu2(bpy(PO3H2)2(μ-ox)]Cl2 complex, denoted as Cu2L, is formed through self-assembly. The formed Cu-Cu diatomic sites effectively promote photogenerated charge separation and CC coupling reactions. This loading process is achieved through hydrogen bonding and π-π stacking interactions, where the -NH4+ on the mCN support surface... x The group forms a P=O…HN hydrogen bond with the -PO3H2 group in Cu2L.

[0067] In some embodiments of this application, the copper-containing compound includes at least one of CuCl2·2H2O, CuSO4·5H2O, and Cu(CH3COO)2·2H2O. Therefore, a wider range of raw materials can be selected, and the cost is lower.

[0068] In some embodiments of this application, the copper complex is a blue solid.

[0069] In some embodiments of this application, the method for preparing a graphitic carbon nitride support includes: using an ammonia-containing organic compound as a precursor, obtaining a graphitic carbon nitride matrix through prepolymerization and a first calcination treatment; and mixing the graphitic carbon nitride matrix with a mixed molten salt for a second calcination treatment to obtain the graphitic carbon nitride support. This allows the introduction of cyano groups into the graphitic carbon nitride support, resulting in a broader visible light absorption.

[0070] In some embodiments of this application, the ammonia-containing organic compound includes at least one selected from urea, melamine, thiourea, dicyandiamide, cyanamide, and cyanuric acid. Therefore, a wider variety of precursors can be used, and the cost is also lower.

[0071] In some embodiments of this application, the prepolymerization temperature is 200℃ to 300℃, for example, 200℃, 250℃, or 300℃, and the first calcination treatment temperature is 450℃ to 650℃, for example, 450℃, 500℃, 550℃, 600℃, or 650℃. Prepolymerization can promote the initial polycondensation of the precursor, reduce excessively rapid volatilization caused by direct high-temperature calcination, and simultaneously repair structural defects, improve crystallinity, and enhance stability through the first calcination treatment.

[0072] In some embodiments of this application, the temperature of the second calcination treatment is 500℃~800℃, for example, 500℃, 600℃, 700℃ or 800℃, etc., and can be carried out in a vacuum-sealed quartz tube with a vacuum degree ≤10. -3 Pa. This is beneficial for improving the crystallinity of the graphitic carbon nitride support.

[0073] In some embodiments of this application, the mass ratio of the graphitic carbon nitride matrix to the mixed molten salt is 1:(2.5-10), for example, it can be 1:2.5, 1:5, 1:7.5 or 1:10, etc. This can increase the reaction rate and reduce raw material waste.

[0074] In some embodiments of this application, the mixed molten salt includes a mixed molten salt of sodium chloride and lithium chloride (NaCl / LiCl), a mixed molten salt of lithium nitrate and potassium nitrate (LiNO3 / KNO3), a mixed molten salt of lithium carbonate and potassium carbonate (Li2CO3 / K2CO3), or a mixed molten salt of lithium chloride, potassium chloride, and lithium carbonate (LiCl / KCl / Li2CO3). Different combinations will have different melting points, but the melting point of the mixed molten salt is lower than that of the respective individual salts. Therefore, this application selects mixed molten salts to achieve the reaction at a lower temperature.

[0075] In some embodiments of this application, the molar ratio of sodium chloride to lithium chloride in the mixed molten salt of sodium chloride and lithium chloride is 1:(0.5-4), for example, it can be 1:0.5, 1:0.8, 1:1.2, 1:2, 1:2.5, 1:3, 1:3.5, or 1:4, etc. It should be noted that the temperature of the second calcination treatment is related to the molar ratio of NaCl to LiCl in the mixed molten salt system. The melting point of NaCl alone is 801℃, and the melting point of LiCl is 605℃. The mixture of the two forms a binary eutectic system, and its melting point changes with the composition ratio, reaching the eutectic point when the molar ratio of NaCl to LiCl is 1:1.2, at which point the melting point is lowest, approximately 552℃. This facilitates completing the reaction at a lower temperature.

[0076] As an example, the preparation method of graphitic carbon nitride support (mCN) may specifically include the following steps:

[0077] (1) A graphitic carbon nitride matrix (g-C3N4) was prepared by prepolymerization at 250℃ and calcination at 550℃ using urea as a precursor.

[0078] (2) Mix g-C3N4 with a mixed molten salt of NaCl and LiCl at a mass ratio of 1:5, calcine at 550℃ under vacuum for 2 hours, and obtain mCN after acid washing, water washing and drying.

[0079] S2: The precipitate is washed and dried sequentially to obtain the photocatalyst.

[0080] In some embodiments of this application, the specific washing steps may include: First methanol wash: Add 20 mL of fresh methanol, ultrasonically disperse (40 kHz, 2 min), centrifuge at 8000 rpm for 5 min; Second methanol wash: Repeat the above operation. First water wash: Add 20 mL of ultrapure water (resistivity ≥18.2 MΩ·cm), ultrasonically disperse (40 kHz, 2 min), centrifuge at 8000 rpm for 5 min; Second water wash: Repeat the above operation.

[0081] In some embodiments of this application, the specific steps of drying may include: transferring the precipitate to a freeze-drying bottle, placing it in a freeze dryer, setting the parameters (temperature: -50±2℃; vacuum: 10±1Pa; time: 24±0.5 hours) to finally obtain dried photocatalyst (Cu2L / mCN) powder.

[0082] This application uses the above method to assemble a double copper complex onto a graphitic carbon nitride support, thereby obtaining a photocatalyst that combines high efficiency in photogenerated charge separation, high product selectivity, and good stability. Moreover, the raw materials are inexpensive and the process is simple, which effectively reduces product costs and makes it suitable for large-scale industrial production.

[0083] In a third aspect of this application, a method for testing the yield of photocatalytic carbon dioxide reduction is proposed, comprising:

[0084] The photocatalyst of the first aspect of this application or the photocatalyst prepared by the method of the second aspect of this application is dispersed in water to form a suspension;

[0085] The suspension is placed in a quartz reactor and carbon dioxide is introduced into the reactor to purge air.

[0086] A light source is used to irradiate the suspension to carry out a photocatalytic reaction, and the gaseous products are sampled during the reaction.

[0087] Gas phase products were analyzed using an online gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector.

[0088] This application employs an online gas chromatograph equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD) to simultaneously detect hydrocarbon products (such as CH4 and C2H4) and inorganic products (such as CO and H2), enabling precise quantitative analysis of the products. Standardized test conditions ensure data comparability, and precise temperature and flow control guarantee experimental repeatability.

[0089] In some embodiments of this application, the analytical conditions of the online gas chromatograph include: helium as the carrier gas, a flow rate of 5 mL / min to 30 mL / min (e.g., 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, or 30 mL / min); and a column temperature program of 80°C for 5 minutes, followed by a ramp-up to 200°C at 10°C / min. Precise temperature and flow rate control ensures experimental repeatability.

[0090] As an example, a method for testing photocatalytic carbon dioxide reduction may include the following steps:

[0091] (1) Disperse 10 mg of photocatalyst evenly in 100 mL of ultrapure water to form a suspension;

[0092] (2) Transfer the suspension to a 300mL quartz reactor and continuously introduce high-purity CO2 gas (purity ≥99.999%). The gas flow rate is controlled at 20mL / min. Aeration is carried out for 1 hour to fully remove air from the system.

[0093] (3) A 300W xenon lamp light source is used and a 420nm cutoff filter is configured to make the output light wavelength range ≥420nm; it is used to maintain the reaction system temperature at 25±0.5℃, including a constant temperature circulation device and a temperature sensor;

[0094] (4) Turn on the light source to carry out the photocatalytic reaction, and maintain the reaction temperature at 25±0.5℃;

[0095] (5) During the reaction, 1 mL of gaseous product was sampled every hour and analyzed by an online gas chromatograph equipped with FID and TCD detectors. The chromatographic column was TDX-01 (3m×3mm), the carrier gas was high-purity helium (flow rate of 30mL / min), and the column temperature program was: 80℃ for 5 minutes, then increased to 200℃ at 10℃ / min.

[0096] (6) The external standard method was used to perform quantitative analysis of the product. Each sample was measured in parallel three times, and the data error was controlled within ±5%.

[0097] (7) After the reaction is complete, wash the sample with deionized water until there is no residue, freeze-dry for 24 hours to recover the sample, and repeat the above activity experiment.

[0098] In a fourth aspect, this application proposes a system for photocatalytic carbon dioxide reduction, comprising: a photocatalyst as described in the first aspect of this application, a quartz reactor, a gas circulation device, and a xenon lamp light source equipped with a 420nm cutoff filter. Thus, this system can achieve efficient and stable photocatalytic carbon dioxide reduction.

[0099] In some embodiments of this application, the headspace volume of the quartz reactor is 250±5 mL, and the light intensity of the light source is 100±2 mW / cm². 2 The reaction pressure was maintained at 1.00 ± 0.01 atm.

[0100] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0101] Example 1

[0102] 1. Preparation of graphitic carbon nitride matrix (g-C3N4):

[0103] (1) Weigh 20.0g of urea, grind it thoroughly, place it in a 100mL alumina crucible, compact it, and then wrap the alumina crucible tightly with multiple layers of tin foil before placing it in a muffle furnace.

[0104] (2) Calcination process:

[0105] First stage: Increase the temperature to 250℃ at a rate of 5℃ / min and maintain for 1 hour;

[0106] Second stage: Increase the temperature to 550℃ at 3℃ / min and maintain for 3 hours;

[0107] (3) Post-processing:

[0108] After naturally cooling to below 200℃, it is ground to obtain g-C3N4 (denoted as CN).

[0109] 2. Preparation of short-range ordered carbon nitride support (mCN):

[0110] (1) Raw material pretreatment:

[0111] 1) Raw material weighing and proportioning: Accurately weigh 10.00±0.02g of the g-C3N4 powder prepared above. Then weigh the NaCl / LiCl mixed molten salt (purity ≥99.99%) at a mass ratio of 1:5, wherein the molar ratio of NaCl to LiCl is 1:1.2 (based on the principle of ionic radius matching);

[0112] 2) Mixed grinding process: Use a planetary ball mill, with grinding parameters set as follows (speed: 300±5 rpm; time: 120±2 min; ball-to-material ratio: 10:1 (using φ5mm zirconia grinding balls)).

[0113] (2) High-temperature calcination treatment:

[0114] 1) Precursor mixing: Weigh 10.00g of graphitic carbon nitride matrix (g-C3N4) and 50.00g of mixed salt of NaCl and LiCl (molar ratio 1:1), place them in an agate mortar and grind and mix for 30 minutes until uniform;

[0115] 2) Vacuum sealing: The mixed powder is loaded into a quartz reaction tube (Φ50×300mm), and the vacuum system is connected to evacuate to 10... - 3 After Pa, the pipe opening is sealed using an oxyhydrogen flame.

[0116] 3) High-temperature calcination: Place the sealed quartz tube in a muffle furnace and heat it to 550°C at a rate of 10°C / min. Maintain the temperature for 2 hours and then allow it to cool naturally to room temperature.

[0117] 4) Acid washing and purification: Open the quartz tube to take out the product, add 1M hydrochloric acid solution (solid-liquid ratio 1:20g / mL), and treat with magnetic stirring (500rpm) at 25℃ for 24 hours;

[0118] 5) Washing: The acid-washed product is repeatedly centrifuged and washed with deionized water (8000 rpm, 5 minutes / time) until the conductivity of the supernatant is ≤5 μS / cm (measured at 25℃);

[0119] 6) Drying: Place the washed product in a vacuum drying oven and dry at 60°C for 12 hours (vacuum degree 10Pa) to obtain a light yellow mCN powder.

[0120] 3. Synthesis of the double copper complex (Cu2L):

[0121] (1) Solution preparation

[0122] 1) Accurately weigh 272.0 mg of copper chloride dihydrate (CuCl2·2H2O, 1.6 mmol) into a 50 mL beaker, add 40 mL of ultrapure water (resistivity ≥18.2 MΩ·cm), and stir magnetically (300 rpm) until completely dissolved to obtain solution A;

[0123] 2) Accurately weigh 506.4 mg of 2,2'-bipyridine-4,4'-bisphosphonic acid ligand (1.6 mmol) into another beaker, add 20 mL of deionized water preheated to 60 °C, and place it in an ultrasonic cleaner (power 100 W, frequency 40 kHz) for ultrasonic treatment for 10 minutes until completely dissolved to obtain solution B;

[0124] 3) Weigh 100.8 mg of oxalic acid dihydrate (0.8 mmol) into an Erlenmeyer flask, add 20 mL of deionized water, heat in a 40°C water bath and stir (200 rpm) until completely dissolved to obtain solution C.

[0125] (2) Assembly of the reaction apparatus

[0126] Transfer solution A to a 100mL three-necked round-bottom flask, install a reflux condenser, a precision thermometer (±0.1℃ accuracy), and a polytetrafluoroethylene stir bar, and place it in a constant temperature water bath.

[0127] (3) Complex synthesis reaction

[0128] 1) Turn on the constant temperature water bath, raise the temperature to 60±1℃, and adjust the stirring speed to 500rpm;

[0129] 2) Using a constant pressure dropping funnel, add solution B dropwise at a constant rate of 0.67 mL / min over 30 minutes.

[0130] 3) Continue to add solution C dropwise at a precise flow rate of 1 mL / min. After all the solution has been added, maintain the reaction for 4 hours, keeping the temperature fluctuation within ±1℃ throughout the process.

[0131] (4) Product separation and purification

[0132] 1) Immediately after the reaction is complete, transfer the reaction solution to a centrifuge tube, centrifuge at 10,000 rpm for 10 minutes, and discard the supernatant;

[0133] 2) Wash the precipitate three times with ultrapure water preheated to 60℃, centrifuging at 8000rpm for 5 minutes each time;

[0134] 3) Transfer the final precipitate to a freeze-drying bottle and freeze-dry at -50°C and 10Pa vacuum for 24 hours.

[0135] 4. Preparation of Cu2L / mCN photocatalyst:

[0136] (1) Carrier pretreatment

[0137] 1) Accurately weigh 50.0 mg of short-range ordered carbon nitride (mCN) powder and place it in a 100 mL round-bottom flask;

[0138] 2) Add 40 mL of chromatographically pure methanol (HPLC grade, water content ≤0.01%);

[0139] 3) Place the flask in an ultrasonic cleaner, set the ultrasonic power to 150W and the frequency to 40kHz, and ultrasonically disperse for 30 minutes; during the ultrasonic process, manually shake the flask 10 times every 10 minutes (each shake amplitude is about 30°) to ensure that the carrier is completely dispersed.

[0140] (2) Loading of active components

[0141] 1) Accurately weigh the copper complex (Cu2L) powder and add it in three portions according to the designed loading amount (5mg);

[0142] 2) Add the ingredients at 30-minute intervals, maintaining the system temperature at 60±0.5℃ during each addition;

[0143] 3) Use a micropipette (accuracy ±0.1mg) to weigh accurately.

[0144] (3) Isothermal reaction

[0145] 1) Place the reaction system in a precision metal bath and set the temperature to 60±0.5℃;

[0146] 2) Adjust the speed of the magnetic stirrer to 500±10 rpm;

[0147] 3) Strictly control the reaction time to 20±0.1 hours, and check the temperature and stirring status every 2 hours during the process.

[0148] (4) Product separation

[0149] 1) After the reaction is complete, allow it to cool naturally to 25±2℃;

[0150] 2) Transfer the reaction solution to a centrifuge tube and centrifuge at 8000±100 rpm for 5 minutes;

[0151] 3) Carefully discard the supernatant and retain the sediment at the bottom.

[0152] (5) Washing and purification

[0153] First methanol wash: Add 20 mL of fresh methanol, sonicate (40 kHz, 2 min), and centrifuge at 8000 rpm for 5 min; Second methanol wash: Repeat the above operation. First water wash: Add 20 mL of ultrapure water (resistivity ≥18.2 MΩ·cm), sonicate (40 kHz, 2 min), and centrifuge at 8000 rpm for 5 min; Second water wash: Repeat the above operation.

[0154] (6) Drying treatment

[0155] The final precipitate was transferred to a freeze-drying bottle and placed in a freeze dryer. The parameters were set (temperature: -50±2℃; vacuum: 10±1Pa; time: 24±0.5 hours) to finally obtain dry Cu2L / mCN photocatalyst powder.

[0156] 5. Photocatalytic performance testing methods:

[0157] (1) Preparation of reaction system

[0158] 1) A 300mL cylindrical quartz reactor (inner diameter 80.0±0.5mm, height 120.0±1.0mm) was selected, with an optical-grade quartz window (transmittance ≥90%@420nm-800nm) at the top;

[0159] 2) Install a PTFE-coated magnetic stir bar (25mm in length and 8mm in diameter) at the bottom and connect it to a digital speed-controlled stirrer (accuracy ±5rpm);

[0160] 3) The reactor sidewall is equipped with a sampling port (with PTFE septum) and a gas inlet and outlet.

[0161] (2) Light source system configuration

[0162] 1) It adopts a 300W xenon lamp light source (model PLS-SXE300, Beijing Pofilai Technology) and is equipped with a 420nm long-pass filter (cutoff wavelength 420±5nm).

[0163] 2) The light source is 150±5mm away from the quartz window, and the light intensity is calibrated to 100±2mW / cm². 2 .

[0164] (3) Photocatalyst pretreatment

[0165] 1) Accurately weigh 10.0±0.1 mg of photocatalyst into a 10 mL glass vial;

[0166] 2) Add 100 mL of ultrapure water (resistivity ≥ 18.2 MΩ·cm, TOC ≤ 5 ppb);

[0167] 3) Ultrasonic dispersion (40kHz, 150W) for 10±0.5 minutes to form a uniform suspension.

[0168] (4) Construction of the reaction system

[0169] 1) Transfer the suspension to the reactor and seal the system;

[0170] 2) Introduce high-purity CO2 (99.999%, H2O≤3ppm, O2≤2ppm) for 1 hour at a flow rate of 50mL / min;

[0171] 3) Adjust the working flow rate to 20.0±0.5mL / min (controlled by mass flow meter);

[0172] 4) Maintain system pressure at 1.00±0.01 atm (monitored by a precision pressure gauge).

[0173] (5) Temperature control

[0174] 1) Place the reactor in a constant temperature water bath (accuracy ±0.1℃);

[0175] 2) Set the temperature to 25.0±0.5℃ and monitor the temperature of the reaction solution in real time.

[0176] (6) Photocatalytic reaction

[0177] 1) Start timing simultaneously when the xenon lamp is turned on;

[0178] 2) Maintain a stirring speed of 300±5 rpm;

[0179] 3) Take 1.00±0.05mL of gaseous product per hour using an airtight syringe.

[0180] (7) Product Analysis

[0181] 1) Gas chromatograph (GC-2014, Shimadzu) configuration: Column: TDX-01 (3m×3mm); Carrier gas: High purity He (99.999%), flow rate 30±0.3mL / min; Detector: FID (250℃) + TCD (200℃);

[0182] 2) Temperature program: Initially 80℃, hold for 5.0±0.1 minutes; increase to 200℃ at 10℃ / min, and finally hold for 3 minutes;

[0183] 3) External standard method for quantification: Standard gas concentrations: 1 ppm, 5 ppm, 10 ppm, 50 ppm (NIST traceable); each sample is injected in parallel 3 times, RSD ≤ 5%.

[0184] (8) Data Processing

[0185] 1) C2H4 yield calculation:

[0186] Y = (n × V) / (m × t)

[0187] Where, n: C2H4 concentration as determined by GC (μmol / mL), V: reactor headspace volume (250±5mL), m: catalyst mass (g), t: reaction time (h);

[0188] 2) Selective calculation:

[0189]

[0190] Parameter description:

[0191] n(C2H4): Amount of ethylene produced (mol);

[0192] n x The amount of substance of other carbon-containing products (such as CO, CH4, CH3OH, etc.);

[0193] x: The number of carbon atoms in the corresponding product molecule (e.g., x=1 for CO, x=2 for C2H4).

[0194] 6. Catalyst stability test method:

[0195] Each cycle reaction time was set to 4 hours. After the reaction, the catalyst was recovered by centrifugation, washed three times with deionized water, dried under vacuum at 60°C for 2 hours, and then redispersed for the next round of testing. Four cycles of the experiment were conducted.

[0196] Example 2

[0197] The difference from Example 1 is that the loading of the double copper complex is 10 mg, while the other operating steps are the same.

[0198] Example 3

[0199] The difference from Example 1 is that the loading of the double copper complex is 15 mg, while the other operating steps are the same.

[0200] Example 4

[0201] The difference from Example 1 is that the loading of the double copper complex is 20 mg, while the other operating steps are the same.

[0202] Test methods and results:

[0203] (1) The graphitic carbon nitride (CN) matrix was characterized by transmission electron microscopy, such as... Figure 2 As shown, the obtained CN exhibits a typical two-dimensional layered structure.

[0204] (2) By Figure 3The high-resolution transmission electron microscope (HRTEM) image in image a shows that the morphology of carbon nitride changed after treatment, forming a rod-like structure, indicating a change in its crystal form. Furthermore, the lattice fringe pattern (…) Figure 3 From the perspective of b), mCN exhibits a microcrystalline structure, with a distance of approximately 0.22 nm between the two CN layers. This is attributed to the interplanar distance between the (001) planes of the layered carbon nitride crystals. By constructing a locally crystalline short-range ordered structure, charge separation in organic semiconductors can be promoted and migration efficiency improved.

[0205] (3) By Figure 4 The transmission electron microscope (TEM) images show that the Cu2L prepared by the above method has a needle-like cluster structure.

[0206] (4) By Figure 5 The Fourier transform infrared (FT-IR) spectrum shows that it is related to C2O4. 2- The relevant characteristic peaks of the OH and C=O stretching vibrations are located at 3450 cm⁻¹. -1 and 1670cm -1 Approximately [time period], disappearing after the reaction. Simultaneously, 2,2'-bpy-4,4'-(PO3H2)2 [occurs] at approximately 1580 cm⁻¹. -1 Approximately 1650cm -1 At 1365cm -1 The characteristic band at this location exhibits a blue shift (attributed to the asymmetric stretching of the pyridine ring), indicating its interaction with Cu. 2+ Chelation occurs. Furthermore, characteristic peaks associated with the -PO3H2 group were observed in [Cu2(bpy(PO3H2)2]Cl4 at 1157 cm⁻¹. -1 The peak at 1068 cm⁻¹ is the stretching vibration peak of P=O. -1 The peak at 768-978 cm⁻¹ is the PO stretching vibration peak. -1 The characteristic bands represent the stretching vibrations of CP, further illustrating the formation of [Cu2(bpy(PO3H2)2]Cl4(Cu2L).

[0207] (5) By Figure 6 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image. Pairs of bright spots can be clearly seen, representing Cu dimers in Cu₂L.

[0208] (6) By Figure 7The X-ray diffraction (XRD) pattern shows that the original g-C3N4(CN) has two XRD peaks at 2θ = 12.7° and 27.5°, belonging to the (100) and (002) planes of CN, respectively, representing the in-plane structure of the tris-s-triazine repeating unit and the periodic interlayer stacking of the conjugated aromatic system. After molten salt treatment, the (100) plane diffraction peak shifted from 12.7° to 8.2°, which is due to the introduction of cyano groups causing the CN bonds to break and form a short-range ordered structure, resulting in intracrystalline torsion of the original planar structure. In addition, compared with CN, the (002) diffraction peak of mCN shifted from 27.5° to 28.0°, which means that the interplane distance is reduced, which is beneficial to electron transfer between CN layers. With Cu2L loading, characteristic peaks of Cu2L were observed, indicating that Cu2L was successfully loaded onto mCN. Furthermore, the doping of Cu2L into mCN does not change the crystal structure of mCN, because the XRD pattern of Cu2L / mCN photocatalyst does not change significantly compared with pure mCN, indicating that there is no strong interaction between the clusters and mCN.

[0209] (7) By Figure 8 The Fourier transform infrared (FT-IR) spectrum shows that -NH x The bimodal stretching vibration shifts to lower wavenumbers with increasing loading on Cu2L, indicating that -NH x Hydrogen bonds were formed between Cu2L and the P=O of -PO3H2, and stretching vibration peaks of P=O and CP were also observed, further demonstrating the successful loading of Cu2L.

[0210] (8) By Figure 9 The UV-Vis DRS spectrum shows that the mCN prepared by the above method has a wider visible light absorption, with the absorption band edge extending from the original 450 nm to 567 nm. The catalyst color changes significantly (pale yellow → orange-yellow), indicating that the method introduces cyano groups into carbon nitride, opens the heptaazine structural unit, and the extended π conjugation can change the electronic band structure. After loading Cu2L onto mCN, the absorption band edge further extends to 603 nm.

[0211] (9) By Figure 10 The comparison chart of photocatalytic performance shows that CN, under visible light, can only produce CO through CO photoreduction, with a yield of only 13.6 μmol·g⁻¹. -1 ·h -1 The photoreduction of mCN to CO2 under visible light produces only CO, but the yield can reach 226.1 μmol·g. -1 ·h -1This is related to the extended absorption under visible light and the enhanced photoelectric conversion efficiency. When a certain amount of Cu₂L is loaded onto mCN, the yield of CO photoreduction from CO₂ under visible light conditions is significantly reduced, and new gaseous products CH₄ and C₂H₄ appear, with the highest yields reaching 185.1 μmol·g⁻¹, respectively. -1 ·h -1 and 82.00 μmol·g -1 ·h -1 .

[0212] (10) From Figure 11 The stability test results show that the Cu2L / mCN photocatalyst has good cycle stability and still has good photocatalytic activity after 4 cycles.

[0213] (11) From Figure 12 The X-ray diffraction (XRD) pattern shows that the structure of the Cu2L / mCN photocatalyst was not destroyed after four cycles of reaction.

[0214] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A photocatalyst, characterized in that, include: A graphite-phase carbon nitride support and a copper complex, wherein the copper complex is at least partially loaded on the surface of the graphite-phase carbon nitride support; The ligands of the copper bis-copper complex include 2,2'-bipyridine-4,4'-bisphosphonic acid; In the conjugated framework of the graphitic carbon nitride support, the cyano group is bonded to the carbon atom site of the triazine ring in the form of end modification. The double copper complex is coupled to the surface of the graphitic carbon nitride support through a combination of hydrogen bonding and π-π stacking.

2. The photocatalyst according to claim 1, characterized in that, The mass ratio of the graphite phase carbon nitride support to the double copper complex is 1:(0.1~0.4).

3. A method for preparing the photocatalyst according to any one of claims 1 to 2, characterized in that, include: The copper complex and the graphite-phase carbon nitride support were dispersed in methanol and stirred to obtain a precipitate. The precipitate was washed and dried sequentially to obtain the photocatalyst.

4. The method according to claim 3, characterized in that, The method for preparing the double copper complex includes: A copper-containing compound, 2,2'-bipyridine-4,4'-diphosphonic acid, and oxalate dihydrate were mixed in a molar ratio of (1.995-2.005):(1.995-2.005):1 to obtain a mixture. The mixture was reacted at 60℃~80℃ and pH 3~5 for 3h~10h, and then dried to obtain the double copper complex.

5. The method according to claim 4, characterized in that, The copper-containing compound includes at least one of CuCl2·2H2O, CuSO4·5H2O, and Cu(CH3COO)2·2H2O.

6. The method according to claim 3, characterized in that, The method for preparing the graphitic carbon nitride support includes: A graphitic carbon nitride matrix was obtained by using nitrogen-containing organic compounds as precursors through prepolymerization and a first calcination treatment. The graphite-phase carbon nitride matrix is ​​mixed with a mixed molten salt and subjected to a second calcination treatment to obtain the graphite-phase carbon nitride support.

7. The method according to claim 6, characterized in that, The nitrogen-containing organic compound includes at least one of urea, melamine, thiourea, dicyandiamide, cyanamide, and cyanuric acid.

8. The method according to claim 6, characterized in that, The prepolymerization temperature is 200℃~300℃, and the first calcination treatment temperature is 450℃~650℃; and / or, The temperature of the second calcination treatment is 500℃~800℃.

9. The method according to claim 6, characterized in that, The mass ratio of the graphite phase carbon nitride matrix to the mixed molten salt is 1:(2.5~10).

10. The method according to claim 6 or 9, characterized in that, The mixed molten salt includes a mixed molten salt of sodium chloride and lithium chloride, a mixed molten salt of lithium nitrate and potassium nitrate, a mixed molten salt of lithium carbonate and potassium carbonate, or a mixed molten salt of lithium chloride, potassium chloride and lithium carbonate.

11. The method according to claim 10, characterized in that, The molar ratio of sodium chloride to lithium chloride in the mixed molten salt of sodium chloride and lithium chloride is 1:(0.5~4).

12. A method for testing the yield of photocatalytic carbon dioxide reduction, characterized in that, include: The photocatalyst according to any one of claims 1 to 2 or the photocatalyst prepared by any one of claims 3 to 11 is dispersed in water to form a suspension; The suspension is placed in a quartz reactor and carbon dioxide is introduced into the quartz reactor to purge air. The suspension was irradiated with a light source to carry out a photocatalytic reaction, and the gaseous products were sampled during the reaction. The gaseous products were analyzed using an online gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector.

13. The method according to claim 12, characterized in that, The analytical conditions of the online gas chromatograph include: The carrier gas is helium, and the flow rate is 5 mL / min to 30 mL / min; The column temperature program was to maintain 80℃ for 5 minutes and then increase to 200℃ at a rate of 10℃ / min.

14. A system for photocatalytic carbon dioxide reduction, characterized in that, include: The photocatalyst, quartz reactor, gas circulation device, and xenon lamp light source equipped with a 420nm cutoff filter as described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen defect / oxygen doped small-size crystalline carbon nitride photocatalyst

    CN116899609A